Comparative analysis of glucose and fructose tolerance in two marine fishes: effects on insulin secretion and acute hypoxia tolerance - Ma, Qiang; Xu, Houguo; Limbu, Samwel Mchele; Wei, Yuliang; Liang, Mengqing (Frontiers in Marine Science, 2023)
Carbohydrates are a common and economical energy source in animal feeds. However, most fish show a persistent postprandial hyperglycemia after intake of a high-carbohydrate diet. Unfortunately, the mechanism of glucose metabolism in fish is still unclear. In the present study, tiger puffer (Takifugu rubripes) and turbot (Scophthalmus maximus) were intraperitoneally injected or orally administered with glucose or fructose (500 mg/kg body weight) to evaluate the ability of fish to utilize carbohydrates. Afterwards, serum glucose, fructose, pyruvate, insulin levels, and acute hypoxia tolerance were measured. Our results showed increased serum glucose level and then decreased post intraperitoneal injection with glucose, and reached a peak after 0.5 hours in turbot and 1 hour in tiger puffer. Tiger puffer had significantly lower liver glycogen, serum glucose, fructose, pyruvate, and insulin contents than turbot. Glucose and fructose only induced insulin secretion in turbot, but did not change serum insulin level in tiger puffer. Glucose was a stronger stimulator of insulin than fructose in the two marine species. Both intraperitoneal injection and oral fructose intake increased serum glucose level, while intraperitoneal or oral glucose also increased serum fructose level. Intraperitoneal injection of glucose promoted absorption and utilization of glucose in the blood more effectively than oral glucose intake. In addition, turbot and tiger puffer were intolerant to acute hypoxia, whereas supplementation with glucose or fructose improved hypoxia tolerance in the two marine fishes by activating anaerobic glycolysis. Taken together, our results provide important scientific information for understanding the mechanism for glucose and fructose utilization and improving hypoxia tolerance in fish.